Metal‐Free Hydrosilylation Polymerization by Borane Catalyst. Issue 49 (16th October 2015) - Kim, Dong Wook; Joung, Seewon; Kim, Jeung Gon; Chang, Sukbok
Abstract: The first example of metal‐free hydrosilylation polymerization between dienes and disilanes is developed by using a borane catalyst, B(C6 F5 )3 to replace precious transition‐metal‐based systems. Under the easy‐to‐handle and mild conditions, a step‐growth polymerization of two readily available diene and disilane units was achieved with high degrees of polymerization. Various combinations of dienes and disilanes produced polycarbosilanes with a broad range of structures and properties. Abstract : The borane supremacy : The first example of metal‐free hydrosilylation polymerization between dienes and disilanes is developed by using a borane catalyst, B(C6 F5 )3 to replace precious‐metal‐based systems. Under the easy‐to‐handle and mild conditions, various combinations of dienes and disilanes produced polycarbosilanes with a broad range of structures and properties.